Cellular Senescence In White Adipose Tissue of Obese Mice - Nova Eininta Sitepu; Sry Suryani Widjaja (Talenta Publisher, 2023)
Obesity is defined as excessive fat accumulation that presents as risk factor for various chronic diseases such as diabetes, cardiovascular disease, hypertension, hyperlipidemia, and cancer. The number of obese population has reached 1 trillion people worldwide and is expected to increase at 42% of the world population until 2030. Excess calories in obesity increase the formation of Reactive Oxygen Species (ROS) that cause DNA damage. DNA damage results in inhibition of the cell cycle and lead to cellular senescence. The mechanism of cell senescence caused by cell cycle inhibition can occur through the cellular senescence pathway by p53/p21 WAF1/CIP1 and p16INK4A / pRB. White adipose tissue is an appropriate reservoir to study of cellular senescence. White adipose tissue of obese model mice showed that there was cellular senescence with marked increase in p21 and p16 gene expression in obese mice